PENGARUH PEMBERIAN ENDORPHINE MASSAGE TERHADAP INTENSITAS NYERI PADA IBU BERSALIN KALA I FASE AKTIF (Jurnal Kesehatan Siliwangi, 2022)
Labor is the process of releasing a baby which is marked by uterine contractions, causing pain during the process before the baby is born. Labor pain that arises more often and for longer can cause the mother to be nervous, afraid and tense and even stressed which results in the release of excessive hormones such as adrenaline, catecholamines and steroids. The use of non-pharmacological management can be done because it is affordable, effective and without side effects and can control feelings, strength and can increase comfort during labor with endorphin massage. This evidence-based case report aims to analyze the results of the action of giving endorphin massage with pain intensity in the first stage of labor. This technique is performed with light massage from the left and right shoulders by forming a V letter towards the tailbone repeatedly when contractions occur during labor. The article search method uses 2 databases, namely: Google Scholar and PubMed with publications in the last 5 years. After reviewing the journal, it was found that there was an effect of giving Endorphin Massage on the intensity of pain in pregnant women in the first stage of the active phase.